To convert the equation \( 11x - 8y = -48 \) from standard form to slope-intercept form (which is \( y = mx + b \)), we need to solve for \( y \).
Starting with the equation:
\[ 11x - 8y = -48 \]
- First, isolate the term involving \( y \):
\[ -8y = -11x - 48 \]
- Next, divide every term by \(-8\) to solve for \( y \):
\[ y = \frac{-11x}{-8} + \frac{-48}{-8} \]
This simplifies to:
\[ y = \frac{11}{8}x + 6 \]
So the slope-intercept form of the equation is:
\[ y = \frac{11}{8}x + 6 \]
Here, the slope \( m \) is \( \frac{11}{8} \) and the y-intercept \( b \) is \( 6 \).